2021
DOI: 10.3390/ma14174823
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Plastics Used for Protection against COVID19—The Influence of Chemical Disinfection by Alcohol on the Properties of ABS and PETG Polymers

Abstract: In this paper, the influence of disinfection on structural and mechanical properties of additive manufactured (AM) parts was analyzed. All AM parts used for a fight against COVID19 were disinfected using available methods—including usage of alcohols, high temperature, ozonation, etc. —which influence on AM parts properties has not been sufficiently analyzed. During this research, three types of materials dedicated for were tested in four different disinfection times and two disinfection liquid concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Catalin Gheorghe Amza [ 64 ] analyzed the effect of ultraviolet radiation on test specimen aging. Krzysztof Grzelak et al [ 74 ] discussed the effect of chemical disinfection using alcohol, and in [ 75 ], Olivier Oth et al described the low-temperature sterilization methods using hydrogen peroxide.…”
Section: Effect Of Multiple Aging and Sterilization Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalin Gheorghe Amza [ 64 ] analyzed the effect of ultraviolet radiation on test specimen aging. Krzysztof Grzelak et al [ 74 ] discussed the effect of chemical disinfection using alcohol, and in [ 75 ], Olivier Oth et al described the low-temperature sterilization methods using hydrogen peroxide.…”
Section: Effect Of Multiple Aging and Sterilization Processesmentioning
confidence: 99%
“…Krzysztof Grzelak et al analyzed the effects of another sterilization method—alcohol disinfection—on the print properties [ 74 ]. The tests included three materials, i.e., PETG filament with color pigment and without additives and ABS for medical purposes, which is a dedicated material for medical applications.…”
Section: Effect Of Multiple Aging and Sterilization Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Common sterilization methods of medical equipment include steaming (autoclaving), dry heat treating, ultrasonic sterilization, or exposure to agents, such as hydrogen peroxide or ethylene oxide [21][22][23][24][25]. Work by Grzelak et al, on the effects of alcohol disinfection on ABS and PETG parts showed that PETG parts can lose 20% of their tensile strength after exposure to sterilizing alcohol [26]. In a study by Popescu et al [27], repeated hydrogen peroxide vapor and low temperature gas plasma sterilization were studied, as autoclaving the 3D printed acrylonitrile butadiene styrene parts deforms the material.…”
Section: Introductionmentioning
confidence: 99%
“…Other than atmospheric effects, chemical effects have also been analyzed. For example, in the context of the COVID-19 pandemic, Grzelak et al analyzed the effects of alcohol disinfection on ABS and PETG parts meant for use in a medical setting and concluded that PETG parts can lose up to 20% of their tensile properties after repeated sterilization [ 36 ]. Moreno Nieto et al investigated the design of parts made from PLA and PETG for water environments and found that PLA degrades significantly more than PETG due to its organic nature [ 37 ].…”
Section: Introductionmentioning
confidence: 99%